Primary malignant melanoma of the female urethra: A case report - Viktoriya Boncheva; Omid Yassaie; Andrew Kennedy-Smith (Urology Case Reports)
Primary malignant mucosal melanoma of the female urethra is extremely rare and associated with high recurrence rates and exceptionally poor 5-year survival. Due to its rarity, treatment strategies are heterogenous and often extrapolated from the treatment of other more common types of melanomas. Herein, we describe a case of malignant melanoma of the urethra in a Caucasian female.